The Influence of Traditional and Digital English Textbooks on Students’ Learning Interest - Ahmad Samat; Geminastiti Sakkir; Hasriani G (PT Ahan Group Publisher, 2026)
The purpose of this research is to analyse the influence of using traditional and digital English textbooks to improve students' learning interest. The research employed a quantitative method using a pre-experimental one-group pretest–posttest design. The subjects were 29 students of class XII.1 at SMAN 9 Tana Toraja, selected through cluster random sampling. Data were collected through pre- and post-observations. The results showed that the use of traditional textbooks increased the average learning interest score from 13.93 to 16.45, with a significance value of 0.000 (< 0.05), an effect size of 0.69 (medium category), and an N-Gain in the low category. Meanwhile, the use of digital textbooks increased the score from 15.76 to 23.55, with a significance value of 0.000 (< 0.05), an effect size of 1.84 (large category), and an N-Gain in the high category. Thus, both traditional and digital textbooks have a significant influence on improving students’ learning interest.